2010
DOI: 10.1016/j.poly.2010.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of methanol substituted lanthanum halides

Abstract: The first study into the alcohol solvation of lanthanum halide [LaX 3 ] derivatives as a means to lower the processing temperature for the production of the LaBr 3 scintillators was undertaken using methanol (MeOH) Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 100 publications
(103 reference statements)
2
16
0
Order By: Relevance
“…Our exploration of cerium-halide-based compounds has led to the synthesis of several new cerium-halide-containing materials exhibiting unique structural motifs that form via halide bridging between CeX n centers that are further modified via coordinated 16 15 (19) 13.6787 (15) 13.5954 (10) 18.0529 (18) 5.7157 (5) b/Å 21.1043 (13) 23.760 (2) 20.156 (2) 20.7910 (15) 26.421 (3) 11.3696 (9) c/Å 22.7005 (14) 26.488 (2) 21.192 (2) 22.1835 (15) 28.507 (3) 13.3140 (11) α/deg 68.3360 (10) 81.209 (2) 104.428 (2) 104.9620 (10) 90.00…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our exploration of cerium-halide-based compounds has led to the synthesis of several new cerium-halide-containing materials exhibiting unique structural motifs that form via halide bridging between CeX n centers that are further modified via coordinated 16 15 (19) 13.6787 (15) 13.5954 (10) 18.0529 (18) 5.7157 (5) b/Å 21.1043 (13) 23.760 (2) 20.156 (2) 20.7910 (15) 26.421 (3) 11.3696 (9) c/Å 22.7005 (14) 26.488 (2) 21.192 (2) 22.1835 (15) 28.507 (3) 13.3140 (11) α/deg 68.3360 (10) 81.209 (2) 104.428 (2) 104.9620 (10) 90.00…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, there are contradictory opinions about the stoichiometry of the equilibrium solid phase for the range Ho to Lu; it is either the isostructural monoclinic LnBr 3 ·6H 2 O or monoclinic LnBr 3 ·8H 2 O phase [ 9 – 12 ]. In the case of iodides, isostructural orthorhombic LnI 3 ·9H 2 O was identified for the lanthanide range of La to Er and isostructural monoclinic LnI 3 ·8H 2 O for the range of Tm to Lu [ 10 ]; however, different ranges of the solid solute existence were reported [ 11 , 12 ]. It is a well-known fact that structures and stoichiometries of YBr 3 and YI 3 hydrates resemble those typical for lanthanides, but crystals of ScBr 3 and ScI 3 hydrates are dissimilar compared with the corresponding lanthanide compounds.…”
Section: Solubility Data For Rare Earth Metal Bromides and Iodides Inmentioning
confidence: 99%
“…Likewise, the lighter Ln iodides dehydrate gradually according to the following reaction chain: whereas DyI 3 ·9H 2 O, HoI 3 ·9H 2 O, ErI 3 ·8H 2 O, TmI 3 ·8H 2 O, YbI 3 ·8H 2 O, and LuI 3 ·8H 2 O decompose to the anhydrous LnI 3 salts in one step according to Heiniö et al [ 22 ]. Crystallographic studies of the hydrates confirmed that they were isostructural: monoclinic P 2 1 / n for LnBr 3 ·8H 2 O (Ho–Lu), triclinic for LnBr 3 ·7H 2 O (La–Pr), monoclinic P 2/ n for LnBr 3 ·6H 2 O (Nd–Dy), orthorhombic Pmma for LnI 3 ·9H 2 O (La–Lu), unindexed (probably monoclinic) for LnI 3 ·8H 2 O (Tm–Lu), monoclinic P 2/ n for LnI 3 ·6H 2 O (La–Tb), and unindexed for LnI 3 ·3H 2 O (La–Nd) [ 10 , 12 , 22 – 24 ]. This detailed information is useful for calculation and depiction of the partial LnBr 3 –H 2 O and LnI 3 –H 2 O phase diagrams.…”
Section: Phase Diagrams At the Water-rich Sidementioning
confidence: 99%
“…Boyles et al have observed similar trends within their series of methanol-substituted lanthanum halides obtaining monomeric and dimeric compounds. 23 Examining the differences in the bond distances of the bridging halides reveals that, in most cases, the polymeric chain with bound water has slightly shorter bridging halide bond distances than the dimers. Even though the alcohol and water ligands are neutral donors, their coordination greatly impacts the topological outcome of the structure.…”
Section: Structural Comparisons and Factorsmentioning
confidence: 99%